Dynamics of fecal coliform bacteria along Canada's coast. (April 2023) - You, Shuai; Huang, Xiaolin; Xing, Li; Lesperance, Mary; LeBlanc, Charles; Moccia, L. Paul; Mercier, Vincent; Shao, Xiaojian; Pan, Youlian; Zhang, Xuekui
Abstract: The vast coastline provides Canada with a flourishing seafood industry including bivalve shellfish production. To sustain a healthy bivalve molluscan shellfish production, the Canadian Shellfish Sanitation Program was established to monitor the health of shellfish harvesting habitats, and fecal coliform bacteria data have been collected at nearly 15, 000 marine sample sites across six coastal provinces in Canada since 1979. We applied Functional Principal Component Analysis and subsequent correlation analyses to find annual variation patterns of bacteria levels at sites in each province. The overall magnitude and the seasonality of fecal contamination were modelled by functional principal component one and two, respectively. The amplitude was related to human and warm-blooded animal activities; the seasonality was strongly correlated with river discharge driven by precipitation and snow melt in British Columbia, but such correlation in provinces along the Atlantic coast could not be properly evaluated due to lack of data during winter. Highlights: Sparse fecal pollution data were collected across 15, 000 sites along Canada's coast. Longitudinal geospatial distributions of bacterial levels over decades were studied. Functional Principal Component Analysis revealed two major annual patterns. Human and wild-life activities related to the geospatial bacterial amplitudes. River discharge and precipitation related to the temporal changes of fecal bacteria.